FORMATION OF STUDENTS' COMPETENCES IN TEACHING NATIVE LANGUAGE IN PRIMARY GRADES - Sh. Murataliev (American Journals, 2023)
In this article, primary school students gives a brief opinion about the formation of competences in students and their types in the teaching of mother tongue science.
Keywords: Linguistic competence, speech competence, basic competence, phonetics, lexicology, word structure, word formation, morphology, syntax, punctuation, speech styles, grammatical rules.